21 RARE CASE OF NECROTIZING FASCIITIS DUE TO GROUP C STREPTOCOCCUS. (1st January 2006) - Godkar, D.; Sircar, P.; Maccario, D.; Niranjan, S.; Recco, S. R.
Abstract : Background: Over the last couple of decades group C streptococci have been increasingly implicated in a variety of conditions. When these organisms are isolated from the blood, especially in the absence of overt focal disease, an active search should be initiated for an underlying disease process in an obscure area. To our knowledge this is only the second reported case of necrotizing fasciitis due to streptococcus C infection. Case Report: We present here a case of a teenager who had a history of fall and had erythema with severe pain and edema in both lower extremities. There were blisters over the erythematous areas, ranging from 1 mm to a few centimeters in size, with several having accompanying oozing. The patient had a fasciotomy done within 24 hours of admission. Culture reports from wound swab as well as the tissue biopsy grew group C streptococci sensitive to penicillin. Overall, the patient received 10 days of intravenous penicillin therapy and was discharged home after complete recovery. Discussion: Group C streptococci generally include four species: Streptococcus equilismus, Streptococcus zooepidemicus, Streptococcus equi, and Streptococcus dysgalactiae . Of these the first three are group C beta-hemolytic streptococci. These organisms have been recognized as a common cause of infection in animals but rarely cause infections in humans. Infections caused by group C streptococci predominantly lead to endocarditis, but there have been discrete reports of bacteremia, puerperal infections, lymphadenitis, tonsillitis, meningitis, pericarditis, cellulitis, UTI, septic arthritis, glomerulonephritis, and osteomyelitis. Factors predisposing patients to group C infections are old age, male sex, underlying medical condition including cardiovascular disease, diabetes mellitus, cirrhosis, chronic alcoholism, bone and joint disease, dermatologic processes, and immunocompromised state. Diagnosis of an infection caused by group C or G streptococci is made by identification of the organism in culture.